Model-Independent Bounds on Kinetic Mixing - Anson Hook; Eder Izaguirre; Jay G. Wacker (Advances in High Energy Physics)
New Abelian vector bosons can kinetically mix with the hypercharge gauge boson of the Standard Model. This letter computes the model-independent limits on vector bosons with masses from 1 GeV to 1 TeV. The limits arise from the numerous